Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Matematika dengan menggunakan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) pada SDN 2 Selat Dalam Kuala Kapuas Tahun Pelajaran 2016/2017: Efforts to Improve Student Learning Outcomes in Mathematics Subjects by using the Teams Games Tournament (TGT) Cooperative Learning Model at 2 Strait Elementary Schools in Kuala Kapuas 2016/2017 Academic Year - Rizki Nur Anisa; Agung Riadin (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This study aims to (1) find out the increased activity of students in teaching and learning activities using the cooperative learning model of the Teams Games Tournament (TGT) type (2) knowing the improvement in mathematics learning outcomes for fourth grade students of SDN 2 Selat in Kuala Kapuas after using Teams Games Tournament (TGT) model. The type of research used by researchers is Classroom Action Research (CAR) which seeks to solve the problems faced in the current situation. Analysis The subjects of this study were 24 students, namely nine men and 15 women. Technical data analysis uses qualitative and quantitative data analysis. The results showed that: (1) the activities of students with the implementation of the Teams Games Tournament (TGT) model became better and improved in each cycle. In the first cycle the activities of students gained scores with an average of 2.87 with sufficient categories and increased in the second cycle with an average value of 3.75 with good grades, (2) there was an increase in Mathematics learning outcomes through the use of Teams Games Tournament models ( TGT) wherein the first cycle obtained an average value of 40 with classical completeness of 29.16% and increased in the second cycle with an average value of 78 with artistic integrity of 91.6%.